BEM/OQM Formulation to Simulate Crack Problems - Vera Tudela, C.A.R.; Fontes, E.F.; Telles, J.C.F. (Trends in Computational and Applied Mathematics, 2008)
Over the last few years the Boundary Element Method (BEM) has been successfully applied to linear elastic fracture mechanics problems (LEFM), involving static and dynamic cases. An approach to solve LEFM problems is presented in this work. The Numerical Green’s Function is used at the fundamental solution together with the Operational Quadrature Method. Proceeding this way, there is no need to discretize the unloaded crack surface and the convolution integral is substituted bya Quadrature formula whose weights are computed using the Laplace transform of the fundamental solution and a linear multistep method. This solution strategy is here implemented to deal with problems associated with the scalar wave equation.